The Influence of Entrepreneurial Orientation and Absorptive Capacity on Business Performance through Marketing Capability in Small and Medium Enterprises Selling Pecel Lele in Bekasi City - Aulia Azzahra; Salsabila Rahmadini; Sonia Silastia (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
This study investigates the effects of entrepreneurial orientation and absorptive capacity on business performance, with marketing capability as a mediating variable among pecel lele small and medium enterprises (SMEs) in Bekasi City, Indonesia. A quantitative research design was employed using Structural Equation Modeling (SEM) with AMOS. Data were collected from 570 pecel lele SME owners through structured questionnaires using a five-point Likert scale. The findings reveal that entrepreneurial orientation and absorptive capacity have positive and significant effects on marketing capability. Moreover, entrepreneurial orientation and marketing capability significantly enhance business performance. However, absorptive capacity does not directly affect business performance, but exerts an indirect influence through marketing capability. These results indicate that marketing capability plays a central mediating role in translating entrepreneurial orientation and absorptive capacity into improved business performance. This study contributes to the dynamic capability literature by providing empirical evidence from traditional culinary SMEs and offers practical implications for strengthening marketing strategies to achieve sustainable performance.